A study on the knowledge management readiness in organization: a case study at Sekolah Menengah Kebangsaan Datuk Patinggi Haji Abdul Gapor, Stampin / Salwa Materang - Materang, Salwa (2013)
This study was undertaken to examine the Knowledge Management Readiness in organization. Knowledge is information that is contextual, relevant and actionable. Implementation the Knowledge Management in Organization can increase organization performance, effectiveness and sharing the knowledge thought out the organization.